2006
DOI: 10.1186/1476-4598-5-71
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid and butyrate induce apoptosis in human cancer cells through inhibition of gene expression of Akt/protein kinase B

Abstract: Background: In eukaryotic cells, the genomic DNA is packed with histones to form the nucleosome and chromatin structure. Reversible acetylation of the histone tails plays an important role in the control of specific gene expression. Mounting evidence has established that histone deacetylase inhibitors selectively induce cellular differentiation, growth arrest and apoptosis in variety of cancer cells, making them a promising class of anticancer drugs. However, the molecular mechanisms of the anti-cancer effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 53 publications
3
31
0
1
Order By: Relevance
“…It has been reported that HDAC inhibitors may cause Akt depletion through modulation of gene expression [16] and inhibit Akt phosphorylation through disruption of HDAC-PP1 (protein-phosphatase 1) complex [17]. In this study, we aimed to determine the relationship between HDAC and Akt under the inhibitory effect of MPT0E028.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that HDAC inhibitors may cause Akt depletion through modulation of gene expression [16] and inhibit Akt phosphorylation through disruption of HDAC-PP1 (protein-phosphatase 1) complex [17]. In this study, we aimed to determine the relationship between HDAC and Akt under the inhibitory effect of MPT0E028.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence show that HDAC inhibitors, such as valproic acid and butyrate, impede Akt1 and Akt2 expression, which leads to Akt deactivation and apoptotic cell death [16]. In another study, Chen et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VPA was found to be an effective inhibitor of histone deacetylases and has been shown to induce anti-tumor effects by modulating cellular pathways, including cell cycle arrest, apoptosis, angiogenesis, metastasis, differentiation, and senescence [27]. The antitumor effect of VPA in cervical cancer can be explained by either the hyper-acetylation of p53 protein, protecting it from degradation by E6 and increasing p53 activity; or via the inhibition of Akt1 and Akt2 expression, which results in apoptotic cell death [28,29]. Acetylation of p53 is a process that occurs in response to DNA damage and stress and is necessary for p53 transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Their main virtue lies in their ability to regulate the expression of specific genes involved in proliferation, differentiation, and apoptosis (Chen et al 2006). Because of their biological similarities to cancer cells, stem cells have also been tested for responses to HDACi, especially in terms of stem cell specialization.…”
Section: Introductionmentioning
confidence: 99%